Effect of electrochemical oxidized kerosene on flotation rate of difficult-to-float fine coal. Issue 1 (31st March 2022) - Zhang, Tao; Zhang, Hongbo; Liu, Xiang; Yang, Huifen
ABSTRACT: In order to recover difficult-to-float fine coal, flotation rates of full-size coal are tested using electrochemical oxidized kerosene as a collector. The flotation rate of coal using oxidized kerosene is higher than that of adopting conventional kerosene. However, its flotation product contained more ash due to poor selectivity of oxidized kerosene. The maximum recovery and flotation rate constant of the model were calculated by Curve Fitting Tool in MATLAB software, and the correlation coefficient R 2 of each model is obtained. It is found that the classic first-order kinetic model is the most suitable model for the flotation of kerosene and oxidized kerosene.